Presumed Consent for Organ Donation: An Incoherent Justification - Formoso, Vicente; Marina, Sílvia; Ricou, Miguel (Acta Bioethica, 2021)
The difference between supply and demand of transplantable organs is a global problem, and one of the most discussed measures aiming to solve it is the implementation of a presumed consent (opt-out) policy in cadaveric organ donation. This type of system is controversial when it comes to its direct effects on organ donation rates as well as its ethical base. We aim to present the latest perspectives concerning the ethical implications of the policy, especially regarding consent: its need, the coherence of presuming it and the policy’s capacity to fulfill its requirements. From a community perspective, we advocate a default change in societies with an opt-out system, with a strong population education in that direction. The potential rights of family objection are also approached as well as the differences between theoretical discussion and concrete application of public policy.